Analisis Bonus Demografi Terhadap Pertumbuhan Ekonomi di Pulau Jawa - Wardani, Natalia Ayu (Jurnal Ilmu Ekonomi JIE, 2024)
This research aims to analyse and determine the effect of the demographic bonus on Economic Growth on the Island of Java. This research uses quantitative methods and a panel data regression analysis model, with the best model being fixed effects (FE). Simultaneously, the human development index, population, and open unemployment rate influence the gross regional domestic product in 6 provinces on the island of Java. Partially, the dependency ratio variable positively and insignificantly affects the gross regional domestic product. The human development index positively and significantly affects gross regional domestic product. The population and open unemployment rate negatively and significantly affect the gross regional domestic product. Stakeholders and related agencies are needed to increase the gross regional domestic product on the island of Java, especially in each region, by paying attention to factors that influence economic growth.